Permasalahan Sekitar Qada' dan Qadar - Syed Abdul Rahman, Syed Mohammad Hilmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
This article tries to present some major polemical issues related to human destiny together with its explanation based on the Quranic and the Prophetic tradition. The interpretation and clarification by some Muslim scholars on the issue is also given.